Echocardiographic comparison between left ventricular non-compaction and hypertrophic cardiomyopathy. (1st February 2017) - Haland, Trine F.; Saberniak, Jørg; Leren, Ida S.; Edvardsen, Thor; Haugaa, Kristina H.
Abstract: Background: Modern imaging technology has improved detection of left ventricular non-compaction cardiomyopathy (LVNC). Hypertrophic cardiomyopathy (HCM) shares morphological features with LVNC, but prognosis and treatment strategies differ between LVNC and HCM. Methods and results: We aimed to compare global and regional LV myocardial function in LVNC and HCM. We hypothesized that apical function is reduced in LVNC due to the embryonic reduced compaction of the apex. We studied 25 patients with LVNC (47 ± 14 years) according to current criteria, 50 with HCM (47 ± 14 years) and 50 healthy individuals (49 ± 19 years). By echocardiography, we assessed maximal wall thickness (MWT) and LV ejection fraction (EF). Numbers of trabeculations were counted from 3 apical views. Global longitudinal strain by speckle tracking echocardiography was calculated from a 16 LV segments model. LV basal (6 segments) and apical (4 segments) longitudinal strains were averaged. MWT was thinner, EF lower and trabeculations were more pronounced in LVNC compared to HCM (all p < 0.001) but with no significantly differences in LV global longitudinal strain (− 15.1 ± 6.1 vs. − 16.8 ± 3.7, p = 0.14). Function by longitudinal strain increased significantly from base to apex in HCM (− 14.9 ± 4.3% vs. − 19.5 ± 4.7%, p < 0.001) and in healthy controls (− 20.0 ± 1.9% vs. − 21.8 ± 2.9%, p < 0.001), but not in LVNC (− 14.7 ± 6.4% vs. − 15.7 ± 7.2%, p = 0.35). Conclusions: Increased number of trabeculations, thinner MWT and lower EF were characteristics of LVNC. Myocardial function was homogeneously reduced in LVNC, while an apical to basal gradient with relatively preserved apical function was present in HCM. These characteristics may help to discriminate between LVNC and HCM.